Analisis Perkembangan Masa Usia Dini Berumur 5 Tahun - Ramadhan Lubis; Wulan Hijriayani; Syahidah Awaliah Bintang; M. Fahri; Maya Salsabila; Apuannisa Hasibuan; Azizatul Habibah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This growth and development takes place simultaneously, although both do not occur simultaneously within an individual, let alone between individuals. For example, there are babies who can walk at the age of 11 months, but there are also babies who can only walk after they are 24 months old. There are even identical twins who are born with different weights and heights.